Pierre Rousselot, El problema del amor en la Edad Media, Madrid, Cristiandad, 2004, 190 pp. - Etchebehere, Pablo R. (2006)
Fil: Etchebehere, Pablo R. Pontificia Universidad Católica Argentina; Argentina